1990
DOI: 10.1093/oxfordjournals.annonc.a057716
|View full text |Cite
|
Sign up to set email alerts
|

Responses and toxic deaths in Phase I clinical trials

Abstract: This review analysis consists of the antitumor activity and toxic deaths reported in single agent Phase I clinical trials using cytotoxic compounds published from 1972 to 1987. A total of 6639 patients with a variety of solid tumors and hematological malignancies were accrued in 211 trials studying 87 compounds. The median number of patients per trial was 28 (range: 7-111) and the median of the median ages reported in the individual trial was 56 (range of individual age: 2 to 93 years). Ten percent of the tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
74
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(77 citation statements)
references
References 2 publications
2
74
1
Order By: Relevance
“…A recent systematic review, however, has questioned whether participation in clinical trials is of any benefit to participants (Peppercorn et al, 2004). Various studies have reported that the chance of therapeutic response for those volunteering to take part in phase I trial is less than 5% (Estey et al, 1986;Decoster et al, 1990;Von Hoff and Turner, 1991;Smith et al, 1996;Roberts et al, 2004). In phase II clinical trials, the overall objective response rate (partial and complete) is also usually low.…”
mentioning
confidence: 99%
“…A recent systematic review, however, has questioned whether participation in clinical trials is of any benefit to participants (Peppercorn et al, 2004). Various studies have reported that the chance of therapeutic response for those volunteering to take part in phase I trial is less than 5% (Estey et al, 1986;Decoster et al, 1990;Von Hoff and Turner, 1991;Smith et al, 1996;Roberts et al, 2004). In phase II clinical trials, the overall objective response rate (partial and complete) is also usually low.…”
mentioning
confidence: 99%
“…Despite the emphasis on evaluation of side effects, and determination of a maximum tolerated dose (MTD), tumour responses remain an important secondary end point. Reported response rates for phase I trials are generally between 1 and 10% (Estey et al, 1986;Decoster et al, 1990;Bachelot et al, 2000) with most responses seen at 80 -120% of the recommended phase II dose (Von Hoff and Turner, 1991). Cytotoxic drugs that do not show antitumour activity in phase I trials rarely undergo further evaluation (Von Hoff and Turner, 1991;American Society of Clinical Oncology, 1997;Sekine et al, 2002).…”
mentioning
confidence: 99%
“…In addition, in phase I trials, early cohorts of patients are treated at very low and sometimes ineffective dosages. The overall response rate in phase I trials is low (Estey et al, 1986;Decoster et al, 1990;Von Hoff and Turner, 1991;Penta et al, 1992;Itoh et al, 1994). Furthermore, physicians as investigators conducting phase I trials of anti-cancer agents must always be vigilant in safeguarding the patients' best interests when confronted with ethical issues (e.g.…”
mentioning
confidence: 99%